Approved estimates 1992 of Imo State of Nigeria - Imo State of Nigeria; Imo State Nigeria (Owerri: Imo State Nigeria, 1992)
The total Budget proposal for the state in the 1992 fiscal year is estimated at one billion, three hundred and sixty-six million, nine hundred and thirty three thousand and sixty six naira.
aia 19/02/2019
Loans
Keywords: Nigeria --Imo State; Expenditure-- Public; Finance Public; Budget